1993
DOI: 10.1046/j.1365-2648.1993.18020246.x
|View full text |Cite
|
Sign up to set email alerts
|

Client satisfaction, extended intervention and interpersonal skills in community mental health

Abstract: Some reservations have been expressed about the use of the concept of client satisfaction in relation to clients' views of services received. There has also been little research on clients' perspectives of mental health work. This paper explores client satisfaction with extended intervention from practitioners based at a community mental health centre. Considerable differences are identified between satisfied and not satisfied clients in the service received and their perception. These relate clearly to the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 4 publications
(3 reference statements)
5
42
0
6
Order By: Relevance
“…Participants in this study might have believed that expressing their dissatisfaction and negative feelings about the care they received would disturb the harmony. In addition, many studies have shown that patient satisfaction results were often skewed to the positive responses, especially with older patients, and the instruments used may not be sensitive enough to detect differences between groups of patients (32)(33)(34). Therefore, the results of this study should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 90%
“…Participants in this study might have believed that expressing their dissatisfaction and negative feelings about the care they received would disturb the harmony. In addition, many studies have shown that patient satisfaction results were often skewed to the positive responses, especially with older patients, and the instruments used may not be sensitive enough to detect differences between groups of patients (32)(33)(34). Therefore, the results of this study should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 90%
“…Although client satisfaction surveys can reflect unrealistic expectations, research on mental health service users shows that they can effectively discriminate between services that differ in quality (Lebour, 1983;Sheppard, 1993). The sample size in this study was small but reflected local services similar to those in any treatment centre which caters for a mixed semi-urban and rural population.…”
Section: Discussionmentioning
confidence: 93%
“…Second, regarding gaps in communication, Sheppard [40] suggested that both nurses and patients are sending more information than is conveyed through verbal or non-verbal messages. However, a perception gap-namely, a communication gap-occurs if that additional information is not received.…”
Section: Nurse-patient Perception Gaps Arising From Conflict a Four mentioning
confidence: 99%